Modulatory effect of the 5-HT1A agonist buspirone and the mixed non-hallucinogenic 5-HT1A/2A agonist ergotamine on psilocybin-induced psychedelic experience - Pokorny, Thomas; Preller, Katrin H.; Kraehenmann, Rainer; Vollenweider, Franz X. (European neuropsychopharmacology, 2016)
The mixed serotonin (5-HT) 1A/2A/2B/2C/6/7 receptor agonist psilocybin dose-dependently induces an altered state of consciousness (ASC) that is characterized by changes in sensory perception, mood, thought, and the sense of self. The psychological effects of psilocybin are primarily mediated by 5-HT2A receptor activation. However, accumulating evidence suggests that 5-HT1A or an interaction between 5-HT1A and 5-HT2A receptors may contribute to the overall effects of psilocybin. Therefore, we used a double-blind, counterbalanced, within-subject design to investigate the modulatory effects of the partial 5-HT1A agonist buspirone (20mg p.o.) and the non-hallucinogenic 5-HT2A/1A agonist ergotamine (3mg p.o.) on psilocybin-induced (170µg/kg p.o.) psychological effects in two groups (n=19, n=17) of healthy human subjects. Psychological effects were assessed using the Altered State of Consciousness (5D-ASC) rating scale. Buspirone significantly reduced the 5D-ASC main scale score for Visionary Restructuralization (VR) (p<0.001), which was mostly driven by a reduction of the VR item cluster scores for elementary and complex visual hallucinations. Further, buspirone also reduced the main scale score for Oceanic Boundlessness (OB) including derealisation and depersonalisation phenomena at a trend level (p=0.062), whereas ergotamine did not show any effects on the psilocybin-induced 5D-ASC main scale scores. The present finding demonstrates that buspirone exerts inhibitory effects on psilocybin-induced effects, presumably via 5-HT1A receptor activation, an interaction between 5-HT1A and 5-HT2A receptors, or both. The data suggest that the modulation of 5-HT1A receptor activity may be a useful target in the treatment of visual hallucinations in different psychiatric and neurological diseases. •Effects of 5-HT1A and 5-HT1A/2A agonists on psilocybin-induced psychedelic experience.•5-HT1A agonist buspirone reduces psilocybin-induced visual hallucinations in humans.•Buspirone but not ergotamine abolishes the subjective effects of psilocybin in humans.•The 5-HT1A receptor may be a useful target in the treatment of visual hallucinations.